Assessment of early and late implantation failure of teeth: A single-center experience with 297 implanted teeth - Munir Salih, Haydar; Al-Nimer, Marwan S.M; Mohammed, Nawres Bahaa (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Background: Early and late failure of teeth implantation usually attributed to local conditions of the teeth, risk factors, surgical procedures whether 1-stage or 2-stage, quality of prosthetic materials, and the surgeon ‘profession. Objectives: This study aimed to assess the early and late failure rate of dental implantation. Materials and methods: This prospective, single-center study done in the Consultant Clinic of Dental Implant in the Department of Dentistry at the University College of Al-Rafidain in Baghdad-Iraq during 2017-2020. A total number of 141 patients (80 females and 61 males) were included in the study. A total number of 297 teeth were implanted using a 1-stage and 2-stage procedure. Results: Sixteen patients were managed with 1-stage and 125 patients with a 2-stage procedure. The early failure rate was 30 out of 297 implanted teeth, while the late failure rate was negligible. Smoking and diabetes mellitus as risk factors of implantation failure constituted small percentages. Conclusion: It concludes that early failure of teeth implantation is not a serious complication, while the late failure is negligible. Moreover, a 2-stage procedure is as effective as a 1-stage procedure.